126k views
3 votes
Binomial expression ​

Binomial expression ​-example-1
User Benny Chan
by
4.8k points

2 Answers

3 votes

Answer:

(3, - 2 ) and (- 2, 2 )

Explanation:

(8)

2x + y = 4 → (1)

x + 3y = - 3 → (2)

Multiplying (2) by - 2 and adding to (1) will eliminate the x- term

- 2x - 6y = 6 → (3)

Add (1) and (3) term by term to eliminate x

0 - 5y = 10

- 5y = 10 ( divide both sides by - 5 )

y = - 2

Substitute y = - 2 into either of the 2 equations and solve for x

Substituting into (1)

2x - 2 = 4 ( add 2 to both sides )

2x = 6 ( divide both sides by 2 )

x = 3

solution is (3, - 2 )

---------------------------------------------

(9)

3x + 5y = 4 → (1)

x + 3y = 4 → (2)

Multiplying (2) by - 3 and adding to (1) will eliminate the x- term

- 3x - 9y = - 12 → (3)

Add (1) and (3) term by term to eliminate x

0 - 4y = - 8

- 4y = - 8 ( divide both sides by - 4 )

y = 2

Substitute y = 2 into either of the 2 equations and solve for x

Substituting into (2)

x + 3(2) = 4

x + 6 = 4 ( subtract 6 from both sides )

x = - 2

solution is (- 2, 2 )

User Alex Mazzariol
by
4.5k points
5 votes

Answer

2.(2,1)

3. (2,2)

Explanation:

Given,

2.2x+y=4

x+3y=_3

sol

2x+y=4..... equation i

x+3y=_3 ....eq ii

eq ii of 2 multiple the eq i

2x+y=4

2x+6y=_6

_ _ +

__________

o+ 5y = 10

y =10÷5

y = 2 ans

y valu put the eq 1

2x+y=4

2x+2=4

2x=4_2

2x=2

x=2÷2

x=1

3.

sol

3x+5y=4..... eq 1

x+3y=4 ..... eq 2

eq 2 multiple eq 1. 3

3x+5y=4

3x+9y=12

_ _ _

___________

0x+4y=8

4y=8

y=8÷4

y=2 ans

the y value put the eq 1

3x+5y=4

3x+5×2=4

3x+10=4

3x=10_4

3x=6

x=6÷3

×=2 ans

User Rajender Joshi
by
4.8k points